Intermittent-Contact Heterodyne Force Microscopy: A Novel Approach to Monitor Nanoscale Events - Cuberes, M. Teresa (Current Research Progress in Physical Science Vol. 9, 2025)
Recent developments in Atomic Force Microscopy (AFM) have shown the possibility of obtaining subsurface information using ultrasound. Heterodyne Force Microscopy (HFM) integrates Ultrasonic Force Microscopy (UFM) with Waveguide-UFM, where both the sample and the cantilever are excited at slightly different ultrasonic frequencies. Heterodyne Force Microscopy opens up a way to monitor nanoscale events with high temporal sensitivity from the quasistatic cantilever mechanical-diode response, taking advantage of the beat effect. Here, a novel heterodyne ultrasonic force method is proposed, in which the cantilever is driven in amplitude-modulation mode, at its fundamental flexural eigenmode. The measurements have been implemented by appropriately modifying a commercial AFM instrument (NANOTEC). Ultrasonic vibration in the megahertz range is additionally input at the tip-sample contact from the cantilever base and from the back of the sample. The ultrasonic frequencies are chosen in such a way that their difference is coincident with the second cantilever eigenmode. In the presence of ultrasound, cantilever vibration at the difference frequency is detected. Similarly, to heterodyne force microscopy, it is expected that the phase response yields information with increased sensitivity due to the beat effect.